(untitled) (مجلة جامعة اللاذقية - سلسلة العلوم الأساسية, 2018)
جمعت من شاطئ جبلة عينات من الأسماك المحلية خلال الفترة الممتدة من 30/10/2000 وحتى 2001/12/15 تتضمن الأنواع التالية: (بوري Chelon sp.، زليق Sparisoma sp.، منوري Olada sp.، غريبة Sigonus sp.، إسفنج Balistes sp.، نايلون Sargocentron sp. ، عروسة البحرCoris sp.) وحددت الفحوم الهيدروجينية متعددة النوى العطرية (PAHs) في الأنسجة العضلية لهذه الأسماك.بعد استخلاصها ودراستها كيفياً وكمياً باستخدام تقانة الكروماتوغرافيا الغازية GC-FID. تراوحت تراكيز الفحوم الهيدروجينية العطرية في أنواع الأسماك المدروسة بين قيم دون عتبة الكشف (not detected) و 152.6 ng/g (dry wt. ) وقد سجلت أعلى التراكيز في أنسجة النوعين غريبة والبوري والتي بلغت 152 ng/g (dry wt. )، 101 ng/g (dry wt.)على الترتيب. Some local fish species, which have been collected from Jableh coast during that period (30/10/2000-15/12/2001), include:( Chelon sp., Sparisoma sp., Olada sp., Sigonus sp., Balistes sp., Sargocentron sp., Coris sp. .) For determination of concentration Polycyclic Aromatic Hydrocarbons (PAHs) in studied muscle fish. The (PAHs) were extracted and studied qualitatively and quantitatively by using GC-FID technique. The concentration of (PAHs) in the studied fish species ranged between (not detected) and (152.6 ng /g dry wt.). the highest concentration has been registered in tissues relating to Chelon sp. And Sigonus sp. Reached (152.6 ng /g and 101 ng /g), respectively.